2002 IEEE International Symposium on Circuits and Systems. Proceedings (Cat. No.02CH37353)
DOI: 10.1109/iscas.2002.1009786
|View full text |Cite
|
Sign up to set email alerts
|

On dynamic delay and repeater insertion

Abstract: In deep sub-micron technologies, as the wires are placed ever closer and signal rise and fall times go into the sub-nano second region, increased cross talk has implications on the data throughput and on signal integrity. Depending on the data correlation on the coupled lines, the delay can either decrease or increase. Here we show that in uniform coupled lines, the response for several important switching configurations has a dominant pole characteristic. This allows easy prediction for the average, worst-cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Crosstalk has become the most critical concern in modern sub-10 nm integrated circuits [ 14 ]. This coupling causes problems that can be addressed by various methods like shielding [ 15 , 16 , 17 , 18 , 19 , 20 ], inserting repeaters [ 21 , 22 , 23 , 24 , 25 ] or buffers [ 26 , 27 , 28 , 29 , 30 , 31 ], duplication [ 32 ] and crosstalk avoidance code (CAC) [ 33 , 34 , 35 , 36 ]. Insertion of buffers and shielding has more area cost when compared to duplication or CAC [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crosstalk has become the most critical concern in modern sub-10 nm integrated circuits [ 14 ]. This coupling causes problems that can be addressed by various methods like shielding [ 15 , 16 , 17 , 18 , 19 , 20 ], inserting repeaters [ 21 , 22 , 23 , 24 , 25 ] or buffers [ 26 , 27 , 28 , 29 , 30 , 31 ], duplication [ 32 ] and crosstalk avoidance code (CAC) [ 33 , 34 , 35 , 36 ]. Insertion of buffers and shielding has more area cost when compared to duplication or CAC [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…All lines are uniformly coupled to two aggressor lines, except the two comer-most lines which are coupled to one aggressor. It has been shown that the dominant time constant approximation for the worst-case 50% delay for such lines is accurate to over 95% [3]. Eq.…”
Section: Line Delaymentioning
confidence: 99%
“…The exact effect of cross-talk on delay depends on the switching alignment of the aggressors with respect to the victim. In [l] and [3] we give an analysis of delay in such uniformly coupled lines with different switching pattems. Since in general, it is necessary to design for the worst- The rest of this document is structured in this manner.…”
Section: Introductionmentioning
confidence: 99%
“…This would amount to roughly the same wiring resources per channel for both systems, as the repeater system needs shields between the signal lines to avoid a severe eye degradation. When there would be no shields, then crosstalk between the neighboring wires would create a large dynamically varying delay [152] of as much of 260ps peak to peak, as visible in Table 8.1.…”
Section: Comparison With Repeatersmentioning
confidence: 99%